PUBLIC TRANSPORTATION DRIVER’S AGGRESSIVE BEHAVIOR IN HIGHLY TRAFFIC JAM - Novia Triany; Hendro Prabowo (Jurnal Psikologi, 2008)
The aim of this study is to know the description of public transportation driver aggresive behavior and factors that might be influencing that behavior. This study is a case study with single subject with interview and observation as the method pf the study and helped by some of research tools such as map, graphic test and camera. The participant of this study is public transportation driver Bekasi city. The result shows that factors influencing the aggresive behavior are external and internal factors. And the aggresive behavior that can be seen are territorial, dominant aggresion and aggresive behavior because afraid of something.Key words: traffic jam, public transportation driver, aggresive behavior